Innovationsmanagement fèur Kooperationen; eine instrumentenorientierte Betrachtung - Hagenhoff, Svenja (Universitèatsverlag Gèottingen, 2008)
This publication deals with the management of cooperative innovation activities. The author identifies individual management tasks and designs concrete supporting instruments and methods. The system to be designed by management activities can be understood as an information system which provides the partners of innovation cooperation actionable information. The book is aimed at teachers and students of business administration with a focus on innovation and collaboration management. Practitioners receive a basic insight into the latest management concepts.